Genetic Structure of Wild Bonobo Populations: Diversity of Mitochondrial DNA and Geographical Distribution - Kawamoto, Yoshi (Public Library of Science, 2013)
Bonobos (Pan paniscus) inhabit regions south of the Congo River including all areas between its southerly tributaries. To investigate the genetic diversity and evolutionary relationship among bonobo populations, we sequenced mitochondrial DNA from 376 fecal samples collected in seven study populations located within the eastern and western limits of the species’ range. In 136 effective samples from different individuals (range: 7–37 per population), we distinguished 54 haplotypes in six clades (A1, A2, B1, B2, C, D), which included a newly identified clade (D). MtDNA haplotypes were regionally clustered; 83 percent of haplotypes were locality-specific. The distribution of haplotypes across populations and the genetic diversity within populations thus showed highly geographical patterns. Using population distance measures, seven populations were categorized in three clusters: the east, central, and west cohorts. Although further elucidation of historical changes in the geological setting is required, the geographical patterns of genetic diversity seem to be shaped by paleoenvironmental changes during the Pleistocene. The present day riverine barriers appeared to have a weak effect on gene flow among populations, except for the Lomami River, which separates the TL2 population from the others. The central cohort preserves a high genetic diversity, and two unique clades of haplotypes were found in the Wamba/Iyondji populations in the central cohort and in the TL2 population in the eastern cohort respectively. This knowledge may contribute to the planning of bonobo conservation.